THE SECOND WORLD WAR IN AMERICAN LITERATURE - Fayzullayeva Naimaxon Dilshodbek qizi; Kenjaeva Mukhlisa Bakhodir qizi (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Abstract: In This article expressed the second world war in American Literature. Also the article describes the impact of World War II on American literature and American writers who created during this period.